Kepatuhan Kunjungan Posyandu dan Status Gizi Balita di Posyandu Karangbendo Banguntapan, Bantul, Yogyakarta - Retno Sugiyarti; Veriani Aprilia; Febriana Suci Hati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Malnutrition infants incidence in Indonesia is high about 17.9%. Karangbendo in the last three years has a case of malnutrition infants. The scope of children weighing affect nutritional status of infants. Attendance of health visits in puskesmas Banguntapan III was 63.9% and Karangbendo was 48%. The purpose of this study was to know relationship between health post visits compliance and nutritional status of infants at Karangbendo Banguntapan Bantul, Yogyakarta 2014. This study used descriptive analytic with cross sectional approach. The samples were 40 infants aged 1-5 years that visit Karangbendo health post on 2nd july 2014. The data of health post compliance and nutritional status were obtained by secondary data from KMS. Data were analyzed by Kendall Tau test. The results showed that most of infants aged was 13-36 months about 70% and infants women was 57.5%. The average of health post visits compliance was 70% and category of nutritional status was 72.5% good. The results of the analysis statistics showed that kendall tau value were 0.614 it means that there was a relationship between health post visits compliance and nutritional status of infants. In conclusion, there was a relationship between health post visits compliance and nutritional status of infants at Karangbendo Banguntapan Bantul, Yogyakarta 2014.